Soil Erosion Status of Nepal - Gurung, Sher Bahadur (NUTA Journal, 2021)
Soil erosion is one of the problems in Nepal because about 73 percent of the land surface is mountainous and still tectonically active where 60.43 percent people involved in agricultural activities. The paper assesses the soil erosion status based on ecological region and watershed boundary with population density. The ecological region determined based on elevation and the watershed boundary of Nepal was generated using the Advanced Spaceborne Thermal Emission and Reflection Radiometer–ASTER, 30m resolution Digital Elevation Model (DEM) of NASA's Earth Observing System (EOS) on May 14, 2010. The DEM data was processed using remote sensing technique then hydrological analysis conducted using remote sensing and geographic information system to delineate the watershed boundary. The study generates 19 watersheds based on available soil erosion data. The soil erosion rate of ecological zone and watershed are assessed with population data of Nepal from central bureau of statistic, 2011. There is below 50 people per square kilometer watersheds have average soil erosion rate (about 20 t ha-1/ y-1) and 100 to 500 people per square kilometer watersheds have high soil erosion rate ranges from 27 to 102 t ha-1/ y-1 . These scenarios partial follow the theory of Himalayan degradation. So that there is still environmental degradation is observed and it is needed in detail field based study of Himalaya degradation